For wisdom's sake: collected essays on the book of Ben Sira - Calduch-Benages, Nuria (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2021)
Frontmatter -- Preface -- Contents -- First Publications -- Abbreviations -- Part I. Introductory Questions -- Ben Sira and the Canon of the Scriptures -- Sirach and Inspiration -- Part II. Thematic Essays -- Trial Motif in the Book of Ben Sira with Special Reference to Sir 2,1–6 -- Fear of the Powerful or Respect for Authority in Sirach -- “Cut Her Away from Your Flesh”: Divorce in Ben Sira -- Animal Imagery in the Hebrew Text of Ben Sira -- The Absence of Named Women from Ben Sira’s Praise of the Ancestors -- Polygamy in Ben Sira? -- Good and Bad Wives in the Book of Ben Sira: A Harmless Classification? -- Garment Imagery in the Book of Ben Sira -- The Exodus Traditions in the Book of Ben Sira -- Part III. Essays on Specific Passages -- Amid Trials: Ben Sira 2,1 and James 1,2 -- A Wordplay on the Term mûsar (Sir 6,22) -- Poetic Imagery in the Book of Ben Sira: A Case Study of Sir 21,1–10 -- Emotions in the Prayer of Sir 22,27–23,6 -- Ben Sira 23,27—A Pivotal Verse -- Ben Sira 24,22—Decoding a Metaphor -- Dreams and Folly in Sir 31(34Hb),1–8 -- The Hymn to Creation (Sir 42,15–43,33): A Polemic Text? -- God, Creator of All (Sir 43,27–33) -- Bibliography -- Index of Authors -- Index of References -- Index of Subjects